Studies on soil fertility status of coffee growing regions in Wayanad district - Prasad, P Shiva; Hariyappa, N; Chandrashekar, N; Manonmani, G K; Hareesh, S B; Nadaf, S A; Jagadeesan, M; Venkatesh, D H; Sujatha, K (Journal of Plantation Crops, 2018)
Top soil in Wayanad region is prone to disturbance and erosion, as the coffee growers’ practice scraping, scuffling and cover digging. It is necessary to conserve the inherent fertility of top soil by minimum disturbance during farming operations. Otherwise soil deterioration can become one of the major constraints for crop production in the present day exploitative cultivation of plantation crops. It is well known that nutrient availability is influenced by their distribution in the soil as well as other soil characteristics. Soil fertility is the key to meet the nutrient requirement of the crops. Soil test based nutrient management will increase the crop productivity there by helping to save the fertility. The study, carried out to understand the fertility status of the coffee soils, revealed a higher acidity (98%) with deficiencies of calcium (32%), magnesium (96%) and boron (31%) limiting the coffee productivity in the district. The coffee area in the district is strongly acidic (69%) due to lack of liming and continuous use of acid producing fertilizers. Fifty per cent of soil samples were high in phosphorus which in turn impair the nutrient balance and affects micronutrient absorption by plants. Deficiency of calcium and magnesium affects uptake of other nutrients which upsets cellular functions. In coffee, boron deficiency will reduce the productivity by affecting flowering and fruit set. Amelioration of soil acidity and optimal use of major, secondary and micronutrients are must to enhance coffee productivity in the district. Application of manures and fertilizers based on soil test values will save the fertilizers and also sustain the soil health. Integrated management of plant nutrients is essential to achieve sustainable coffee crop production.